Fracture Fusion on Fast‐Forward: Locally Administered Deferoxamine Significantly Enhances Fracture Healing in Animal Models: A Systematic Review and Meta‐Analysis - Daniel Müller; Jens Klotsche; Magdalena B. Kosik; Carsten Perka; Frank Buttgereit; Paula Hoff; Timo Gaber (Advanced Science)
Abstract Fractures, with a yearly incidence of 1.2%, can lead to healing complications in up to 10% of cases. The angiogenic stimulant deferoxamine (DFO) is recognized for enhancing bone healing when administered into the fracture gap. This systematic review with meta‐analysis investigates the effect of local DFO application on bone healing in rat and mouse models. EMBASE, MEDLINE (PubMed), and Web of Science are systematically searched in January 2024. The study is prospectively registered in PROSPERO (CRD42024492533), and the SYRCLE tool is used to assess study quality and risk of bias. Outcome values contain the primary endpoint bone volume fraction (BV/TV) as well as the secondary endpoints bone volume, tissue volume, bone mineral density, trabecular separation, trabecular thickness, vessel formation and the mechanical properties, assessed by µCT, angiography and mechanical strength tests. Out of 21 included studies, 18 qualify for meta‐analysis, involving 539 animals. DFO‐treated groups exhibit significantly higher BV/TV values (p < 0.0001) compared to controls, with similarly significant improvements in secondary outcomes. These findings highlight the substantial benefit of DFO in promoting bone healing, especially after radiotherapy. Rapid clinical implementation is recommended to help patients at high risk of fracture healing complications.